Me of little faith - Black, Lewis, 1948- (Riverhead Books, 2008)
Lewis Black, the hilariously mad-as-hell Daily Show regular and New York Times-bestselling author, explores how the rules and constraints of religion have affected his life and the lives of us all. Hilarious experiences with rabbis, Mormons, gurus, psychics, and even the joy of a perfect round of golf give Black the chance to expound upon what we believe and why--in the language of a shock jock and with the heart of an iconoclast.--From amazon.com.